A COMPLEMENTARY NOTE TO WELWITSCH’S MAP OF TRAVELLERS IN AFRICA - Albuquerque, Sara (2022)
This note complements the article “Depicting the Invisible: Welwitsch’s Map of Travellers in Africa,” published earlier in Earth Sciences History (Albuquerque and Figueirôa 2018). The note contributes additional information concerning previously unknown names on the map that did not appear in the list of explorers in that earlier publication. The names of ten additional explorers have been deciphered from the map and added to the list from the earlier paper, thanks to the assistance of colleagues. Of the 94 entries originally noted on the map, 88 have now been identified. There is strong correspondence between that list of explorers and the contents of Friedrich Welwitsch’s personal library.